Potret Pendidikan Karakter di Kalangan Keluarga Nelayan - Abdul Khobir (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to describe the implementation of character education, its pattern, as well as the factors influencing the pattern of character education among fisherman families of Pecakaran village, Pekalongan regency. This study belongs to qualitative approach and uses field research. The data were collected through interview, observation, and documentation. The collected data, then, were analyzed by using descriptive qualitative data analysis. The result shows: (1) the implementation of character education among fisherman families can be described from its definition, objectives, materials, and the method used in delivering the character education. (2) the pattern of character education conducted by some parents are educating with full of patience, educating with full of affection, educating with neglect, educating with authoritarian style, and educating with democratic style.. (3) the factors influencing the pattern of character education among the fisherman families of Pecakaran village consist of supporting and inhibiting factors. The supporting factors include habituation, exemplary behavior, environmental circumstance, and self-consciousness, while the inhibiting factors include environmental circumstance, lack of parents’ attention, education, as well as parents' religion